Articulación CUM-Proyecto de desarrollo local: consolidación de la mini-industria de conservas CPA 26 de julio en Abreus - Núñez González, Dra. C. María Rosa; Cabrera Fernández, MSc. Anay; Lamote Mato, MSc. Sergio (Revista Conrado, 2017)
Objetivo: analizar a partir de la caracterización del municipio la propuesta de estrategia para el desarrollo local y cómo contribuye el CUM en articulación con el Proyecto de desarrollo local a la consolidación de las Mini-industrias locales, específicamente en la Mini-industria de conservas de CPA 26 de Julio. Resultados: el análisis realizado, caracterización del municipio y la propuesta estratégica para el desarrollo local permitió establecer la contribución del CUM en articulación con el Proyecto de desarrollo local específicamente en la Mini-industria de conservas de CPA 26 de Julio, asociada a la Empresa Cultivos Varios de Juraguá la cual permitirá la producción de más de 20 surtidos envasados en diferentes formatos, potenciar la producción de conservas y otros alimentos a partir de la autogestión productiva con recursos locales, todo lo cual elevará la calidad de vida de los abreuenses. Palabras clave: Articulación, CUM (Centro Universitario Municipal), proyecto, desarrollo local, mini-industria, CPA 26 de julio en Abreus. ABSTRACT Articulation CUM-Project of local development: Consolidation of the preserved food at the mini-industry Farming Production Unit “26 de Julio” in Abreus has as its main objective the analysis from the characterization of the municipality, the proposal of strategy for the local development and how the CUM (Municipal Academical Center) in articulation contributes with the Project of local development to the consolidation of the local mini-industries, specifically at the preserved food mini-industry Farming Production Unit “26 de Julio”. This work incorporates a characterization of Abreus municipality, as strategy of local development there and consolidation of the CUM in articulation with the Project of local development, the development of the local mini-industries: Specifically Nutritious industries, as the preserved food Mini-Industry Farming Production Unit “26 de Julio”. The results accomplished with the analysis, characterization of the municipality and the strategic proposal for the local development allowed establishing the contribution of the CUM in articulation with the Project of local development specifically at the preserved food Mini-Industry Farming Production Unit “26 de Julio” once the Varied Cultivation Company was associated which will enable the production of Juraguá about over 20 assortments bottled in different formats, increasing the power of the production of preserves and other foods as from the productive auto-step with local resources, all which will raise the abreuenses's quality of life. Keywords: Articulation, CUM (Municipal Academical Center), project, local development, mini-industry, Farming Production Center “26 de Julio” in Abreus